Development of Weblog Based Learning Media in Information and Communication Technology Guidelines - Lenny Erawati; Waskito Waskito; Krismadinata Krismadinata (International Journal of Educational Dynamics, 2020)
This research aims to develop weblog-based learning media on information and communication technology (ICT) guidance and reveal its validity and practicality. This type of research is a research development with a 4-D (Four D) model , namely Define, Design, Develop , and Disseminate . The instrument used was a questionnaire in the form of a questionnaire of validity and practicality. weblog based learning media on information and communication technology guidance is validated by 2 experts, namely 1 material expert and 1 media expert . Practicality weblog-based learning media on information and communication technology guidance is carried out on teachers and students of SM A N 1 Tujuh Koto Sungai Sarik . The results of the validity test show that weblog-based learning media on information and communication technology guidance is included in the valid category. Based on practicality test by the teacher and students of SM A N 1 Tujuh Koto Sungai Sarik shows that the media has a very high practicality category. Based on the results of this study, it can be concluded that the weblog-based learning media on information and communication technology guidance is considered valid and practical .